2018
DOI: 10.1002/jper.17-0365
|View full text |Cite
|
Sign up to set email alerts
|

High‐power, red‐light‐emitting diode irradiation enhances proliferation, osteogenic differentiation, and mineralization of human periodontal ligament stem cells via ERK signaling pathway

Abstract: The results of this study show that 650-nm high-power, red, LED irradiation increases PDLSCs proliferation, and osteogenic differentiation and mineralization, mediated by ERK1/2 activation. These findings suggest that LED may be a useful tool for periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…RUNX2 is an early transcription factor regulating the osteogenic differentiation progress (Kato et al, 2016; Li, Chen, & Zhang, 2015). OSX is also an early osteoblast transcription factor and has a vital role in the differentiation of preosteoblasts into immature osteoblasts (Yamauchi, Kato, & Umeda, 2018). Our results indicated that the expression of OPN, RUNX2, OSX, and COL‐1 were upregulated in CTP‐CM‐induced hPDLSCs as compared with those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 is an early transcription factor regulating the osteogenic differentiation progress (Kato et al, 2016; Li, Chen, & Zhang, 2015). OSX is also an early osteoblast transcription factor and has a vital role in the differentiation of preosteoblasts into immature osteoblasts (Yamauchi, Kato, & Umeda, 2018). Our results indicated that the expression of OPN, RUNX2, OSX, and COL‐1 were upregulated in CTP‐CM‐induced hPDLSCs as compared with those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT induced positive effects on cell proliferation were also observed in cultured normal human keratinocytes, fibroblasts, osteoblasts, mesenchymal and cardiac stem cells, endothelial and HeLa cells. ROS production following LLLT has been demonstrated to be able to induce preodontoblasts as well as preosteoblasts proliferation [4,13,15,21,22,26,47,48,[67][68][69][70], in which Runx2 and Osterix mRNA expression result enhanced by ERK1/2 pathway [71].…”
Section: Lllt Effects On Cellular Respiration and Redox Statementioning
confidence: 99%
“…These cells possess biological characteristics, which resemble the mesenchymal stem cells (MSCs) and are of great value to the study of periodontal tissue regeneration . Therefore, for periodontal tissue regeneration, PDLSCs are considered as the most promising seed cells and have own unique advantages in oral and maxillofacial tissue regeneration . To optimize seed cells, gene regulation must be accomplished, which requires understanding the mechanism of PDLSC differentiation and regulation.…”
Section: Introductionmentioning
confidence: 99%